Risk Analysis of Work Posture and Body Mass Index to Musculoskeletal Disorders among Librarians at Universitas Airlangga - Nugraha, Adellian; Widajati, Noeroel; Guan, Ng Yee; Febriyanto, Eka Cahya; Oktavia, Nurul Dewi (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: Potential ergonomic hazards at work can lead to complaints of musculoskeletal disorders (MSDs). The Global Burden of Disease estimated that, by 2019, there were about 1.71 billion people in the world living with musculoskeletal problems. One of the jobs that has this risk is librarians because their jobs are dominated by static postures. This study aims to determine the correlation between work posture and body mass index (BMI) with MSDs complaints among librarians at Universitas Airlangga. Methods: This study is an analytical observational research with a cross-sectional design. The sample of this study consists of the total population of librarians at Universitas Airlangga that met the inclusion criteria, totaling 28 librarians. Primary data were obtained through the direct distribution of questionnaires to librarians, observations of work posture and musculoskeletal complaints in librarians. The data in this study were analyzed using the Spearman rank correlation test. Results: The research results showed that the level of mild MSDs complaints was reported by 7 librarians (25.0%), moderate complaints by 13 librarians (46.4%), and severe complaints by 8 librarians (28.6%). The statistical test results indicate a strong and positive correlation between work posture and MSDs complaints (r = 0.444), while a weak and positive correlation was found between BMI)(r = 0.222) and years of service (r = 0.158) with musculoskeletal disorders complaints. Conclusion: This study concludes that librarians in high-risk work postures may experience musculoskeletal disorders complaints, especially in the neck, shoulders, and back areas.